2021
DOI: 10.1016/j.heliyon.2021.e06829
|View full text |Cite
|
Sign up to set email alerts
|

Role of emotional intelligence and grit in life satisfaction

Abstract: Background There is a pressing need to study life satisfaction in the context of collectivistic culture, particularly of undergraduate students. Various socio-cultural factors influence the level of emotional intelligence and grit of an individual. Even though a wide array of research on life satisfaction is available, it hasn't been studied in relation to grit and emotional intelligence (as conceptualized by Bar On), both of which can be acquired and enhanced over time. To the best of researcher'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 31 publications
6
27
0
1
Order By: Relevance
“…Also, life satisfaction can be predicted positively by job satisfaction (H2), which is consistent with the other studies [ 39 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. This study proved that emotional intelligence and life satisfaction are interrelated, supporting H3 and previous studies [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Finally, H4 was confirmed indicating that job satisfaction partially plays a mediating role in associating emotional intelligence and life satisfaction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Also, life satisfaction can be predicted positively by job satisfaction (H2), which is consistent with the other studies [ 39 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. This study proved that emotional intelligence and life satisfaction are interrelated, supporting H3 and previous studies [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Finally, H4 was confirmed indicating that job satisfaction partially plays a mediating role in associating emotional intelligence and life satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…Emotional intelligence was also found as a positive predictor of life satisfaction in adolescents [ 31 ], undergraduates [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ], teachers [ 39 , 40 , 41 ], and adults from China [ 42 ] and Australia [ 43 ]. Life satisfaction is one of three core components of subjective well-being and positive and negative affect [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study expand the reports of potential causes of teacher's mental health from other studies (Yang et al, 2019;Halladay et al, 2020;Ain et al, 2021) and also reveal the determinants and mechanisms between emotional intelligence and teachers' mental health. As a result of the analysis which was conducted for examining the direct role of emotional intelligence on mental health was found significant prediction.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have analyzed the relationship between some aspects of emotional intelligence and the configuration and characteristics of social support networks in adolescence. Bar-On’s trait model of Emotional Intelligence emphasizes the fundamental role of emotions in interpersonal relations, where emotion management and control are essential for a beneficial social life [ 59 ]. Concerning emotional awareness, Rowsell et al [ 14 ] studied the ability to identify emotions in the composition of social networks, and found that emotional awareness influences such composition in girls, as the social networks of girls were more likely to be made up of peers of the same gender when they scored high in identification with emotions, while when the scores were low, the girls tended to choose boys for interaction.…”
Section: Introductionmentioning
confidence: 99%